IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY KNOWLEDGE IN THE CIVIL ENGINEERING LABORATORY FACULTY OF ENGINEERING UNG - la Abdul, Barry; Abdul Gani, Hamsu; Purnamawati (Jurnal Vokasi Keteknikan, 2025)
This study aims to analyze the implementation of Occupational Health and Safety (OHS) knowledge in civil engineering laboratories, focusing on the effectiveness of OHS training in improving awareness, knowledge, and practical skills among laboratory users. The research method employed a mixed approach (qualitative and quantitative) through surveys, observations, and interviews with laboratory users. The results revealed that before the training, the average OHS knowledge level was only 40%, with major issues such as a lack of understanding of chemical risks (40%), improper use of Personal Protective Equipment (PPE) (35%), and the absence of clear emergency procedures (50%). After the training, there was a significant increase in OHS knowledge to 75%, along with an improvement in practical skills from 25% to 65%. The training evaluation showed a participant satisfaction rate of 80%, with training objectives such as increased awareness, knowledge, and skills being well achieved. However, challenges such as budget constraints, time limitations, and a lack of OHS experts remain obstacles. This study concludes that regular and structured OHS training is highly effective in improving occupational health and safety in civil engineering laboratories. Recommendations include enhancing training materials, allocating specific budgets, and establishing an OHS team to ensure the sustainability of OHS implementation